Isolation of Dihydrostilbenes from Macaranga Heynei and their Bioactivities - S. Kamarozaman, A; Ahmat1, N; L. Muhammad Low, A; F. Rajab, N; Zamkhuri, Z; Shaameri, Z; Jaafar Sidik, N; D. A. Kamaruzzaman, N (International Journal of Engineering and Technology, 2019)
Macaranga is known to contain abundant sources of prenylated flavonoids and stilbenoids which possessed broad spectrum of biological activities including anti-inflammatory, antimicrobial, antioxidant and cytotoxicity. These species are widely distributed in New Guinea, Borneo and from West Africa to the south Pacific islands. Although Macaranga comprises a large number of species, this genus has not been widely investigated which prompted us to conduct a study on Macaranga heynei. This research is conducted to isolate and characterise the compounds from M. heynei as well as to access the antibacterial and cytotoxicity of the isolates. The purification from the leaves of M. heynei has successfully yielded three dihydrostilbenes which were analysed by means of NMR, UV-Vis, FTIR, MS and comparison with the literature data. These compounds were characterised as laevifolins A (1) and B (2) as well as macarubiginosin C (3). Laevifolin A (1) exhibited good activity against S.cohnii subsp. urealyticum and moderate activity against S.aureus ATCC 25923 with the IC50 values of 11.65 and 27.13 ïM respectively. It also displayed pronounced inhibition against HT-29 cells with an IC50 value of 21.20 ïM. Meanwhile, laevifolin B (2) displayed moderate activity on S.cohnii subsp. urealyticum but strong inhibition against S.aureus ATCC 25923 with the IC50 values of 20.71 and 1.64 ïM respectively.Â